2008
DOI: 10.1016/j.ejcts.2008.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mitral valve-left ventricle dimensions between a beating heart and during saline injection test☆

Abstract: The saline injection test could aid in determining the length of the reconstructed chordae. However, the test may provide inaccurate data of the mitral-LV dimensions due to the flattened annulus and overstretched leaflets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…This fact was proved in our previous report in which strut chordae movement was observed with a high-speed camera, and in other reports of animal experiments. 12,13 However, the results of the present study indicate that the strut chordae do not loosen, although they do extend to a slight degree in synchronization with the cardiac cycle. In the normal heart, we found that the contraction ratio of the strut chordae was 2.4%–3.2%, whereas it was 1.8%–2.2% in the deteriorated heart.…”
Section: Discussioncontrasting
confidence: 56%
“…This fact was proved in our previous report in which strut chordae movement was observed with a high-speed camera, and in other reports of animal experiments. 12,13 However, the results of the present study indicate that the strut chordae do not loosen, although they do extend to a slight degree in synchronization with the cardiac cycle. In the normal heart, we found that the contraction ratio of the strut chordae was 2.4%–3.2%, whereas it was 1.8%–2.2% in the deteriorated heart.…”
Section: Discussioncontrasting
confidence: 56%
“…Besides, in the experimental study of Nonaka et al [8], the distance between the papillary tips and the mitral annular plane remained constant in both SI test and the beating heart respectively. There were, therefore, no significant differences in chords length between the two tests.…”
Section: Discussionmentioning
confidence: 81%
“…A shortening of the transverse annular diameter reducing the intercommissural width is observed intraoperatively. Moreover, the mitral leaflets appeared to bulge more and the coaptation area appeared wider than on an arrested and flaccid heart [8], offering a physiologically faithful intraoperative evaluation model to real conditions of ventricular load and contractility.…”
Section: Operative Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…15 However, because of the annular conformational differences in the arrested and beating heart, discrepancies between direct surgical and intraoperative TEE assessment of valve competency can occur. 17 Surgical resistance to relinquish the immense responsibility of testing valve integrity over to another provider is understandable, particularly considering that in one survey, only 63% of cardiac anesthesiologists had passed the National Board of Echocardiography advanced examination. 11 Of considerable controversy in the MacKay et al study is the trend toward less perioperative TEE use in patients undergoing cardiac valve surgery who were identified as Hispanic.…”
mentioning
confidence: 99%